Comparative Transcriptome Analyses Characterize Expression Signatures Among Males, Females, Neo-Males, and Gynogenetic Females in the Yellow Drum (Nibea albiflora) - Zhu, Qihui; Qin, Zeqian; Chen, Ruiyi; Wang, Ligai; Tan, Peng; Xu, Dongdong (Frontiers in Genetics, 2022)
The yellow drum (Nibea albiflora) is one of the most important marine economic fish in China, and its sexually dimorphic growth makes it preferable for mono-sex culture. Although gynogenesis and neo-male induction techniques have been established, the molecular pathways and regulatory mechanisms of sex determination and maintenance in gynogenetic females and neo-males remains far from fully understood. In this study, the gene expression profiles were investigated in the gonads and brains of wild-type male, wild-type female, neo-male, and gynogenetic female yellow drum using comparative transcriptome analyses. Generally, a total of 52,999 novel transcripts were obtained in RNA-seq, of which 45,651 were isoforms of known protein-coding genes, 1,358 novel protein-coding genes, and 5,990 long non-coding RNAs. We found that the differences between wild-type males and neo-males and between wild-type females and gynogenetic females were relatively small at both the histological and transcriptomic levels, indicating that artificial gynogenesis or hormonal sex reversal may have minimal effects on normal female or male life function, respectively. In the brain, pathways such as ‘Oocyte meiosis’, ‘Cell cycle’, and ‘Riboflavin metabolism’ were found to be significantly enriched. In the gonads, pathways such as ‘Prolactin signaling pathway’, ‘PPAR signaling pathway’, ‘Cholesterol metabolism’, and ‘Jak-STAT signaling pathway’ were found to play important roles in maintaining the regular proliferation and differentiation of females and males in yellow drum. In particular, we found that zp4 might be an effective molecular marker to differentiate between gynogenetic and normal females owing to its unique expression pattern. The results of this study may help to elucidate the molecular mechanisms involved in sex maintenance in the gonads and brain and provide basic data for genetic breeding of the yellow drum.